A Comparative Analysis of DSN-MUI Fatwas Regarding Murabahah Contract and the Real Context Application (A study at Islamic Banking in Aceh) - Ibrahim, Azharsyah; Salam, Abdul Jalil (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The National Sharia Council-Indonesian Ulama Council (DSN-MUI) has issued 11 fatwas (a formal ruling on a point of Islamic law) related to murabahah for parties in economic transactions. However, in the initial study, several indications of the dissonance between the clauses in the fatwa and the practice of Islamic banking were found. This study aims to analyze the application of murabahah contracts in Islamic banking in Aceh. Several Fatwas declared by the National Sharia Council - Indonesian Ulama Council (DSN-MUI) that are related to murabahah were used as an analytical tool to assess the shariah value of the contract in financing practice at Islamic banking in Aceh. This study used a descriptive qualitative method, particularly, a critical study approach. Data were collected using: 1) interviews with bank employees and customers, 2) participant observation in which researchers were directly involved in the process of financing application at several Islamic banks, and 3) documentation studies of resources related to the fatwas. The results showed that the practice of murabahah financing conducted by Islamic banking in Aceh was not fully in accordance with the fatwas stipulated by the DSN-MUI. The results of the analysis showed that the discrepancy lies in the following matters such as ownership of goods, 'coercion' in the use of murabahah contracts, and the inappropriate use of 'wakalah'or contract assistant. The study also revealed that the practice of murabahah in this method has both positive and negative economic implications for banking customers and the banks, especially with regards to profits, calculations of credit ceiling, and customers’ image and trust.